Dissection of the long-range circuit of the mouse intermediate retrosplenial cortex - Yuxiao Li; Miao Ren; Bimin Liu; Tao Jiang; Xueyan Jia; Haili Zhang; Hui Gong; Xiaojun Wang (Communications Biology)
Abstract The retrosplenial cortex (RSP) is a complex brain region with multiple interconnected subregions that plays crucial roles in various cognitive functions, including memory, spatial navigation, and emotion. Understanding the afferent and efferent connectivity of the RSP is essential for comprehending the underlying mechanisms of its functions. Here, via viral tracing and fluorescence micro-optical sectioning tomography (fMOST), we systematically investigated the anatomical organisation of the upstream and downstream circuits of glutamatergic and GABAergic neurons in the dorsal and ventral RSP. The cortical connections of the RSP show laminar organisation in which the input neurons are distributed more in the deeper layers of the upstream cortex. Although different types of neurons have similar upstream circuits, GABAergic neurons show bidirectional connections with the hippocampus, whereas glutamatergic neurons only show unidirectional connections. Moreover, GABAergic neurons receive more inputs from the primary sensory cortex than from the prefrontal cortex and association cortex. The dorsal and ventral subregions have preferred circuits such that the dorsal RSP exhibits spatially topological connections with the dorsal visual cortex and lateral thalamus. The systematic study on long-range connections across RSP subregions and cell types may provide useful information for future revealing of RSP working mechanisms.